Adventures with biology : biology experiments for young people - Bleifeld, Maurice (Springfield, NJ : Enslow Publishers, 1997)
Presents thirty science experiments about biology, specifically dealing with physiology, botany, heredity, and microbiology.
Includes index.
L.A. Recommended Foreign Language.
Science and Children (N.S.T.A.).
6.7.
6.7
5-8
Keywords: Biology -- Experiments -- Juvenile literature; Biology -- Experiments; Experiments; Biology -- Experiments; Experiments